Genome-wide identification evolution and expression of vestigial-like gene family in chicken. Issue 7 (12th December 2022) - Hou, Dan; Qin, Panpan; Niu, Xinran; Li, Tong; Chen, Bingjie; Wei, Chengjie; Jing, Zhenzhu; Han, Ruili; Li, Hong; Liu, Xiaojun; Tian, Yadong; Li, Donghua; et al.
Abstract: Vestigial-like ( Vgll ) genes are widespread in vertebrates and play an important role in muscle development. In this study, we used bioinformatics methods to systematically identify the chicken VGLL family in the whole genome and investigated its evolutionary history and gene structure features. Tissue expression spectra combined with real-time PCR data were used to analyze the organizational expression pattern of the genes. Based on the maximum likelihood method, a phylogenetic tree of the VGLL family was constructed, and 94 VGLL genes were identified in 24 breeds, among which four VGLL family genes were identified in the chicken genome. Ten motifs were detected in the VGLL genes, and the analysis of introns combined with gene structure revealed that the family was conserved during evolution. Tissue expression analysis suggested that the expression profiles of the VGLL family genes in 16 tissues differed between LU Shi and AA broilers. In addition, a single gene ( VGLL2 ) showed increased expression in chickens at embryonic days 10–16 and was involved in the growth and development of skeletal muscle in chickens in the embryonic stage. In summary, VGLL genes are involved in chicken muscle growth and development, which provides useful information for subsequent functional studies of VGLL genes.